Penerapan Teknologi Mesin Pencacah Sampah dan Biodigester untuk Pembuatan Pupuk Organik dan Biogas - Ismail, Ismail; Nusri, Andi Zulkifli; Asmini, Asmini; Herdiansyah, Herdiansyah; Arismanza, Andi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
One of the most prominent natural resources in Congko Village is agricultural land of around 300.72 hectares, while the area of plantation land managed by the Bulu Mappalasae farmer group reaches 101 hectares consisting of 21 hectares of corn land, 63 hectares of cocoa/cocoa land, and 17 hectares of rice fields. The results of the plantation are unsatisfactory, namely for the cocoa plantation which is only able to produce 500kg/hectare/year. One of the obstacles to the lack of productivity of agricultural products is due to the lack of fertilizer, the amount of fertilizer obtained by farmers averages 600kg / hectare, while the fertilizer needed by farmers averages 1 ton / hectare or a total of 63 tons from a land area of 63 hectares. Apart from agricultural activities, there are also livestock activities owned by the community. With the livestock business, the community can make this a potential area. However, the problem in animal husbandry is that livestock waste/dung increases every day and pollutes the environment because it is not managed properly, but if livestock waste/dung can be managed properly, it can provide great benefits to the community such as biogas management from livestock manure which produces gas and organic fertilizer. The solution to the existing problems is to integrate farming and livestock to make organic fertilizer and apply the technology of making biogas from livestock manure. To implement the solution, an implementation method was prepared, namely conducting training and mentoring in making organic fertilizer and managing livestock manure into biogas and organic fertilizer using a bidiogester. From the results of processing waste into organic fertilizer, there are organic fertilizer products that are ready to be applied to agricultural land and produce 3 tons of organic fertilizer / month. And the results of managing livestock manure produce 540kg/month of biogas and 2.3 tons/month of organic fertilizer.